2020
DOI: 10.1186/s12884-020-03150-0
|View full text |Cite
|
Sign up to set email alerts
|

Spiral artery blood flow during pregnancy: a systematic review and meta-analysis

Abstract: Background Downstream remodeling of the spiral arteries (SpA) decreases utero-placental resistance drastically, allowing sustained and increased blood flow to the placenta under all circumstances. We systematically evaluated available reports to visualize adaptation of spiral arteries throughout pregnancy by ultra-sonographic measurements and evaluated when this process is completed. Methods A systematic review and meta-analysis of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…This study demonstrates that SA-PI and -PSV measurements are largely unaffected by SA sample location, as we assessed SA-PI and -PSV in three placental segments and documented no significant change overall with the exception of a single gestational window, which is most probably a statistical variation, rather than a physiologic change. Our finding is consistent with a 2020 meta-analysis examining SA blood flow during pregnancy which found no difference in SA-PI by SA location 24 . Interrogating the SA in the central portion of the placenta is therefore recommended, as it is commonly its thickest portion and thus easier technically.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrates that SA-PI and -PSV measurements are largely unaffected by SA sample location, as we assessed SA-PI and -PSV in three placental segments and documented no significant change overall with the exception of a single gestational window, which is most probably a statistical variation, rather than a physiologic change. Our finding is consistent with a 2020 meta-analysis examining SA blood flow during pregnancy which found no difference in SA-PI by SA location 24 . Interrogating the SA in the central portion of the placenta is therefore recommended, as it is commonly its thickest portion and thus easier technically.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the mean RI values for both SA and IVA were significantly higher in the FGR group in the third trimester compared with pregnancies that did not develop FGR. The fall in SA resistance with gestational age is consistent with the observations of a recent meta-analysis which suggested that the reduction in SA-RI parallels the physiologic trophoblast invasion occurring particularly in the mid-trimester 32 . The increasing IVA resistance with increasing gestational age is difficult to explain physiologically, as we would expect this to mirror changes in the umbilical artery.…”
Section: Discussionsupporting
confidence: 88%
“…Spiral artery PI has been shown to be higher in the first and second trimesters among pregnant women who developed complications (i.e. hypertensive disorders, fetal growth restriction, preterm labor, placental abruption) as compared with uncomplicated pregnancies (1.49 vs 0.80; P < 0.001) 7 . The movement of maternal blood within the placenta has been tracked using ultrasound contrast in 25 pregnant women 9 .…”
Section: Intraplacental Blood Flowmentioning
confidence: 98%
“…The distance between jets increases near the periphery of the placenta and in obstetric complications, such as a small-for-gestational-age fetus and pre-eclampsia 6 . Doppler velocimetry studies of the spiral arteries show a reduction in the pulsatility index (PI) from 0.8 in the first trimester to 0.5 in the second and third trimesters 7 and a similar reduction in the resistance index (first trimester, 0.34; second trimester, 0.28; third trimester, 0.27) (Figure 2) 8 , with no changes in peak systolic velocity (PSV) (first trimester, 0.22 m/s; second trimester, 0.28 m/s; third trimester, 0.25 m/s; P = 0.56) 7 . Spiral artery PI has been shown to be higher in the first and second trimesters among pregnant women who developed complications (i.e.…”
Section: Intraplacental Blood Flowmentioning
confidence: 99%